Treatment of helicobacter pylori contamination in patients with type 2 diabetes mellitus with gastroduodenal disorders - Yuri L. Fedorchenko (Endocrinology Research Centre, 2017)
Background: The treatment of Helicobacter pylori (HP) infection in patients with diabetes mellitus with chronic gastroduodenal disorders is a substantial problem because of its high incidence. Aims: To compare between the effectiveness of triple and optimised consecutive regimens in anti-HP treatment in patients with type 2 diabetes mellitus with gastroduodenal disorders. Materials and methods: The study included 54 patients with diabetes mellitus and 64 healthy individuals (the control group) aged 30–60 years. Gastroduodenal pathology was confirmed by gastroduodenoscopy; HР contamination was confirming using Marshall’s urease method or by finding bacterial antigen in excrements. We studied the dynamics of clinical manifestations using the GSRS scale and showed remission via endoscopy and the effectiveness of HР eradication. We also analysed the effects of anti-HР therapy regimens on the presence of small intestinal bacterial overgrowth syndrome (SIBOS) in patients with diabetes mellitus. SIBOS was diagnosed via the respiratory hydrogen method. Results: The use of an optimised consecutive regimen resulted in HР eradication in 85.7% of patients with diabetes mellitus compared with a 65.3% eradication in patients on the triple therapy. Moreover, clinical improvement and endoscopy-confirmed remission were more frequently observed in patients on the optimised consecutive regimen. A statistically significant decrease in the number of patients with SIBOS was found only in patients who underwent the optimised consecutive therapy regimen. Conclusions: This study showed that the optimised consecutive therapy regimen was more effective than the triple therapy in HP eradication.